The principle of Reformed intertextual interpretation - Song, Young Mog (HTS teologiese studies, 2006)
There has been a growing interest in intertextuality as a hermeneutical category in contemporary current biblical studies. The texture of a particular text is thickened and its meaning extended by its interplay with other texts, especially when the reader recognizes that the repetition of similar phrases and subject matter form part of an integral whole. The concept of intertextuality in this article firstly challenges the traditional approach that assumes that there is one meaning in a text that can be deduced when the author's intention is determined. Secondly, it disagrees with the New Criticism in which only the autonomous text plays the dominant interpretive role. The reader is considered to be merely a passive consumer of the text. Thirdly, it differs from the post-structural/deconstructional way which declares “the death of the author”.